2013
DOI: 10.1292/jvms.13-0189
|View full text |Cite
|
Sign up to set email alerts
|

The Natural PPAR Agonist Linoleic Acid Stimulated Insulin Release in the Rat Pancreas

Abstract: Free fatty acids play an important role in regulating animal insulin secretion response. Acute elevated free fatty acids increased animal insulin secretion and glucose-stimulated insulin secretion. In the present study, we perfused the rat pancreas to explore the effect of unsaturated fatty acids on insulin secretion. The results showed that linoleic acid, γ-linolenic acid and arachidonic acid significantly stimulated insulin secretion. Glucose (10 mM) alone induced a biphasic insulin secretion response. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…P. alliacea contain an unsaturated free fatty acids named linoleic acid which can stimulate insulin secretion and increase glucose-induced insulin secretion in rats in a dose-dependent manner. 8 In addition, in a dose-dependent manner, allantoin compounds are also known can increase insulin secretion and decrease basal blood glucose level. 9 Tannins have also been observed to increase insulin activity and enhance the glucose uptake through mediators of the insulin-signalling pathways, especially in adipocyte.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…P. alliacea contain an unsaturated free fatty acids named linoleic acid which can stimulate insulin secretion and increase glucose-induced insulin secretion in rats in a dose-dependent manner. 8 In addition, in a dose-dependent manner, allantoin compounds are also known can increase insulin secretion and decrease basal blood glucose level. 9 Tannins have also been observed to increase insulin activity and enhance the glucose uptake through mediators of the insulin-signalling pathways, especially in adipocyte.…”
Section: Discussionmentioning
confidence: 99%
“…Linoleic acid and allantoin can stimulate insulin secretion. 8,9 *Correspondence: mustikaarifa@yahoo.com Biomolecular and Health Science Journal. Available at https://e-journal.unair.ac.id/BHSJ DOI: 10.20473/bhsj.v3i1.19129…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the findings for active PAI-1 plasma concentrations and PAI-1 mRNA expression in adipose tissue, after 6 weeks of HFD, fasting insulin levels in serum and HOMA-IR both no longer differed from those found after consumption of the ND, suggesting that subjects might have metabolically adapted to the increased fat intake. Indeed, it has been suggested by the results of animal studies that certain fatty acids — for example, arachidonic acid, γ-linolenic acid, or linoleic acid — may alter insulin release (Gravena et al, 2002; Lai et al, 2013). It further was shown that a long-term intake of a HFD may be associated with a decrease of this effect (Lai et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been suggested by the results of animal studies that certain fatty acids — for example, arachidonic acid, γ-linolenic acid, or linoleic acid — may alter insulin release (Gravena et al, 2002; Lai et al, 2013). It further was shown that a long-term intake of a HFD may be associated with a decrease of this effect (Lai et al, 2013). If similar effects were involved in the present study, and which molecular mechanisms are responsible for the reduction of insulin concentrations and HOMA-IR found when consuming the HFD for an extended period of time, remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Our study further showed that higher proportions of n-6 PUFAs were associated 8 with a lower risk of T2D, concordant with a previous meta-analysis of prospective 9 cohort studies (44). The association may be partly mediated by increasing insulin 0 sensitivity through increasing cellular membrane fluidity (45,46), particularly of 1 skeletal muscle cells and hepatocytes (45,46), and by acting as ligands for 2 peroxisome proliferator-activated receptor gamma (47,48). These hypotheses are 3 supported by a meta-analysis of randomized feeding trials that showed improvements in glucose-insulin homeostasis for dietary PUFA compared to SFA or MUFA (49).…”
mentioning
confidence: 97%